MODEL MAKROEKONOMI TAHUN 2000 - TAHUN 2010 - Satrianto, Alpon; Amar, Syamsul; Aimon, Hasdi (Program Studi Magister Ilmu Ekonomi, 2012)
ABSRACT This study aims to analyze and find out (1) the influence of consumption, investment, government spending, exports and imports to GDP in Indonesia, (2) the influence of disposable income and deposit rates on consumption in Indonesia, (3) the influence of interest rates on investment, GDP , and the rate of investment in Indonesia, (4) the influence of exchange rate and U.S. GDP to exports in Indonesia, and (5) the influence of exchange rate and GDP to imports in Indonesia. This study uses a macroeconomic model developed by Keynes with a simultaneous equation model analysis with Two Stages Least Squared method (TSLS) from the first quarter of 2000 - the first quarter of 2010. The study concluded that (1) consumption, investment, government spending, exports and imports significantly affect the GDP in Indonesia. (2) have a significant disposable income on consumption in Indonesia. (3) the investment rate, GDP, and significantly influence the rate of investment in Indonesia. (4) exchange rate and the GDP of the United States have a significant effect on exports in Indonesia, and (5) exchange rate and GDP have a significant effect on imports in Indonesia. Keyword: GDP, Consumption, Investment, Government Spending, Export, Import, Disposible Income, Invesment Rate, Exchange Rate.